State of the Research on Credentialing. (June 2015) - Lundmark, Vicki; Ingram, Linda
<x xml:space="preserve">Abstract</x> This column is presented to report an update on the status of research on credentialing in nursing by the director of the Institute for Credentialing Research at the American Nurses Credentialing Center. The author presents an overview of the 5 meetings held to explore this topic and recommendations for further study.